The Humanitarian Access Paradox: Data Security in Contested Settings - Searle, Martin (2017)
In complex humanitarian settings, potential data thieves include warring parties. Beyond undermining privacy, data loss risks violating neutrality, an often critical principle for negotiating humanitarian access. Can aid organisations protect that information?